2008
DOI: 10.1002/app.28079
|View full text |Cite
|
Sign up to set email alerts
|

Effects of salts in the Hofmeister series and solvent isotopes on the gelation mechanisms for hydroxypropylmethylcellulose hydrogels

Abstract: The effects of various inorganic salts and isotopic solvents on the thermal gelation behavior of hydroxypropylmethylcellulose (HPMC) in aqueous solutions were examined by micro-differential scanning calorimetry and rheological measurements. It was found that salting-out salts, such as NaCl, promoted the sol-gel transition of HPMC at a lower temperature. An analysis of solvent isotope effects on the changes in the temperature at maximum heat capacity (T m ) with salt concentration showed that interchain hydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 40 publications
3
45
0
Order By: Relevance
“…In the presence of up to 0.4M NaCl, matrices containing HPMC and 8:2 HPMC:PEO, show increased T80 values, but at 0.8M these matrices exhibit a marked acceleration of drug release. This effect has been previously reported in other HPMC matrix formulations [9] and has been attributed to the failure of an effective gel layer diffusion barrier, during the early stages of matrix hydration, as a result of inhibition of polymer swelling through Hofmeister effects [35,36].…”
Section: T80 Valuessupporting
confidence: 68%
See 1 more Smart Citation
“…In the presence of up to 0.4M NaCl, matrices containing HPMC and 8:2 HPMC:PEO, show increased T80 values, but at 0.8M these matrices exhibit a marked acceleration of drug release. This effect has been previously reported in other HPMC matrix formulations [9] and has been attributed to the failure of an effective gel layer diffusion barrier, during the early stages of matrix hydration, as a result of inhibition of polymer swelling through Hofmeister effects [35,36].…”
Section: T80 Valuessupporting
confidence: 68%
“…PEO hydration is reported to be sensitive to salts [35][36][37][38], but in these investigations the threshold concentration was clearly much higher for PEO than for HPMC.…”
Section: T80 Valuesmentioning
confidence: 99%
“…Imaging studies suggested this behaviour arose from sugar-induced suppression of polymer hydration and a subsequent loss of gel layer diffusion-barrier function (Williams et al, 2009). The threshold concentration, S CRIT varied between sugars, and correlated with their ability to disrupt water structure and to suppress the polymer sol:gel transition temperature in a manner analogous to the Hofmeister effects seen with inorganic salts (Alderman, 1984;Liu et al, 2008;Pygall et al, 2009). The concentrations of sugar required to achieve S CRIT (0.5 M-1.15 M) were commonly higher than concentrations found in foods, and were considered unlikely to be encountered in the fed stomach.…”
Section: Introductionmentioning
confidence: 95%
“…The mechanism is considered to involve the re-orientation of water molecules around regions of hydrophobic substitution, and the formation of an insoluble three-dimensional polymer gel network through hydrophobic interactions (Sarkar 1979;Haque and Morris, 1993). More recent advances in our understanding of Hofmeister effects has suggested that ions can directly interact with the hydration sheath of macromolecules (Zhang and Cremer, 2006) and this can be applied to the many historical studies of 'saltingin' and 'salting-out' of HPMC by electrolyte solutions (Touitou and Donbrow, 1982;Mitchell et al, 1990;Kajiyama et al, 2008;Liu et al, 2008).…”
Section: Introductionmentioning
confidence: 98%